2021
DOI: 10.3390/ijerph182312491
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Communication on College Students’ Self–Other Risk Perceptions of COVID-19: A Comparative Study of China and the United States

Abstract: This study aimed to explore cross-country differences in the characteristics and determinations of self–other risk perceptions of the COVID-19 pandemic. We distinguished perceived risk to self from perceived risk to others and subdivided risk perceptions into three levels: personal, group, and societal. We focused on the differential impact of multiple communication channels (i.e., interpersonal communication, traditional media exposure, and new media exposure) on risk perceptions at the three levels. A sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…In China, there is limited research on how people perceive risk from previous infectious disease outbreaks [13] . Most of these studies focus on specific populations, such as older adults [14] , medical staff [15] , college students [16] , or assess perceptions and attitudes in specific periods, such as quarantine [17] . By understanding public perceptions, concerns, and attitudes, it will be possible to develop tailored interventions to encourage preventive measures.…”
Section: Introductionmentioning
confidence: 99%
“…In China, there is limited research on how people perceive risk from previous infectious disease outbreaks [13] . Most of these studies focus on specific populations, such as older adults [14] , medical staff [15] , college students [16] , or assess perceptions and attitudes in specific periods, such as quarantine [17] . By understanding public perceptions, concerns, and attitudes, it will be possible to develop tailored interventions to encourage preventive measures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, collectivism deepens social ties among people and strong social ties motivate people to actively pay attention to external information and share their real-time situations, which increases individual and collective perceived risk [ 9 ]. Yang et al [ 9 ] also indicated that the Chinese who were exposed to interpersonal communication and media would learn more about COVID-19 and increased the perceived risk. Then, perceived risk can decrease mental health [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It suggested that individualism rather than collectivism was a protective factor for depression in Russia, and collectivism promotes maladaptive emotional responses in emotionally unstable individuals in the face of environmental stress, ultimately leading to the emergence of depressive symptoms. Due to an excessive focus on relationships with others, people in collectivist cultures maintain close social relationships and are more focused on sharing and exchanging information with those around them, which leads to an increase in individual and collective perceived risk [ 9 ]. Hence, the impact of collectivism on mental health has not been conclusively established.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional media channels, individuals play the role of passive information receiver, but in new media channels, individuals can be both information receivers and information providers. 34 Considering these differences between traditional media and new media, we investigate the impact of traditional media and new media on people's risk perceptions separately.…”
Section: The Impact Of New Media and Traditional Media On Public Covi...mentioning
confidence: 99%